Interpreting MS Digby 86. A trilingual book from thirteenth-century Worcestershire - Fein, Susanna (Manuscript culture in the British Isles, 2019)
Extravagantly heterogeneous in its contents, Oxford, Bodleian Library, MS Digby 86 is an utterly singular production. On its last folio, the scribe signs off with a self-portrait - a cartoonishly-drawn male head wearing a close-fitted hood - and an inscription: "scripsi librum in anno et iii mensibus" (I wrote the book in a year and three months). His fifteen months' labour resulted in one of the most important miscellanies to survive from medieval England: a trilingual marvel of a compilation, with quirky combinations of content that range from religion, to science, to literature of a decidedly secular cast. It holds medical recipes, charms, prayers, prognostications, magic tricks, pious doctrine, a liturgical calendar, religious songs, lively debates, poetry on love and death, proverbs, fables, fabliaux, scurrilous games, and gender-based diatribes.0That Digby is from the thirteenth century adds to its appeal, for English literary remnants from before 1300 are all too rare. Scholars on both sides of the vernacular divide, French and English, are deeply intrigued by it. Many of its texts are found nowhere else: for example, the French Arthurian Lay of the Horn, the English fabliau Dame Sirith and the beast fable Fox and Wolf, and the French Strife between Two Ladies (a candid debate on feminine politics). The interpretations offered in this volume of its contents, presentation, and ownership, show that there is much to discover in Digby's lively record of the social and spiritual pastimes of a book-owning gentry family